Analisa Retention Karyawan terhadap Kualitas Rekrut Karyawan Baru PT XYZ - Kristian, Yohan; Rahardjo, Jani (Jurnal Titra, 2019)
The research is conducted to analyze the causes of new employee resigning the company. The new employee resigned during 2018 with the working period less than three months. The resigning new employee created loss in time and cost for the company. The analysis is done using paretto diagram to determine the cause that should be solved. The analysis continued using fishbone diagram. There are two factors causing the employee to resign, they are abandonment and performance. Abandonment is caused the employee getting a new job. Performance is caused by the employee having sub par performance. The research on employee performance gives solution to the resigning employee through interviewing based on interest and competence, completing the induction program, recruiting trainer, expanding the size of the training room, and adding tools and system to monitor the materials.